A METHODOLOGICAL MODEL FOR DEVELOPING INFORMATION SECURITY SKILLS IN FUTURE TEACHERS BASED ON ARTIFICIAL INTELLIGENCE TECHNOLOGIES - Mastura Muminova; Juraev Vokhid; Mamirjon Turdimatov (Modern American Journals, 2025)
In recent years, digital technologies have become an integral component of the educational process. Along with this transformation, issues of information security have gained particular urgency, making it essential for teacher-training programs to equip future educators with the ability to guide students toward safe, responsible, and conscious use of the internet. In the online environment, learners are exposed to various risks such as misinformation, breaches of personal data digital violence, and cybercrime. Therefore, future teachers must possess solid methodological preparation in order to effectively teach students the fundamentals of information security.